INCLUSION OF SENIOR CITIZENS IN LIFELONG LEARNING TO REDUCE THE NEGATIVE IMPACT OF POPULATION AGING IN LATVIA SOCIETY - Azamatova, Tatjana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Today, the age structure of the population of Latvia is close to the average for the European Union, but the share of senior citizens is rapidly increasing. Population aging is one of the most significant trends in demographic processes, which brings changes to all areas of society. This article analyses some risks both for seniors themselves and for society resulting from these trends, and the reasons why Latvia is falling behind in addressing these risks. The primary goal of this article is to summarise and interpret a variety of scientific publications and legal documents from a global perspective, also using methods such as monograph analysis, content analysis, descriptive statistics, and compilations of experiences and best practices. The author of the article put forward arguments in favour of the inclusion of seniors in lifelong education in Latvia, as one of the elements of social policy to reduce the negative effects of population aging. According to the author, it is necessary to promote and develop a fully lifelong learning system for seniors in Latvia.